The Queen can do no Wrong: An Examination of the Reign of Queen Elizabeth II in Africa and the Position of the British Monarch with Regard to International Crimes - Aghem Hanson Ekori (Britain International for Academic Research (BIAR-Publisher), 2023)
Queen Elizabeth II would be remembered by many as a great queen who ruled and reigned for more than seven decades. Her seventy years of reigned as the British Monarch has imparted the world and the African continent whom she has visited more any other continent even before she was crowned as the British Queen. Indeed, Queen Elizabeth II was even proclaimed as British Queen while in Africa. Although many African leaders have hailed the Queen for the roles she played as the leader of the Commonwealth besides being the crowned Monarch, others have accused her for colonial crimes and harsh British practises administered by British colonial administration in Africa. Accordingly, the Queen ascended into the throne during the peak of decolonisation of Africa. International law protects the Queen in her capacity as the British Monarch and as the head of state or leader of the Commonwealth nations. This article examines reign of Queen Elizabeth II and argued that the British Monarch is protected by international law rule on immunities as the head of state of the Commonwealth nations and as a Constitutional Monarch of the United Kingdom (UK), despite many accusations from the African continent. Consequently, the immunities accorded by customary international to senior state officials also protects the Queen in her capacity as the British Monarch and as head of state to the Commonwealth nations. It further maintains that the position of the Constitutional Monarch exempts them for committing crimes unlike the British Prime Minister who exercises political power and could be charged and prosecuted for international crimes.